PENGARUH PEMANASAN DANVARIASI CAMPURAN BAHAN BAKAR PREMIUM DAN ETANOL TERHADAP EMISI GAS BUANG KARBON MONOKSIDA (CO) DAN HIDROKARBON (HC) PADA SEPEDA MOTOR YAMAHA VEGA R TAHUN 2009 - Saputra, Firdaus Doni (Jurnal Nosel, 2015)
The purpose of this research were : (1) To knew how the effect of heating premium fuel through a copper pipe installed between the fins of cylinder block to exhaust gas emissions (CO) and (HC) on Yamaha Vega R 2009 motorcycles. (2) To knew how the effect of heating mixture of gasoline and fuel ethanol through a copper pipe installed between the fins of cylinder block to exhaust gas emissions (CO) and (HC) on Yamaha Vega R 2009 motorcycles. (3) To know the value of the levels exhaust gas emissions (CO) and (HC) on the effect of heating fuel were installed between the fins of cylinder block Yamaha Vega 2009 motorcycles.This research used a descriptive quantitative method. The sample used was Yamaha Vega R 2009 motorcycles with the numbere of machine 4D71261848. The data obtained from the value of CO and HC with percentage variation mixture of premium ethanol E0, E5, E10, E15, E20, E25, E30 using a method without heating fuel and heating fuel using 1, 2 and 3 pipes. The data obtained from this research included in the tables and displayed in a graph, and then analyzed.Based on this research can be conclude : (1) The highest levels (CO) when heating fuel on the 1 pipe, while the lowest levels (CO) when without heating fuel. The highest levels (HC) when heating fuel on the 2 pipe, while the lowest level (HC) when heating fuel on the 1 pipe. (2) The highest levels (CO) when heating fuel on the E0 variation of fuel while the lowest levels (CO) when heating fuel on the E0 variation of fuel. The highest levels (HC) when heating fuel on the E30 variation of fuel while the lowest levels (HC) when heating fuel on the E5 variation of fuel. (3) The highest levels exhaust gas emissions (CO) is 1.216 (% vol) and The lowest levels exhaust gas emissions (CO) is 0.083 (% vol). While the highest levels exhaust gas emissions (HC) 877 (ppm vol) and the lowest levels exhaust gas emissions (HC) is 99 (ppm vol).